Are humans encroaching too much? man versus bear - Sanyal, Aparesh; Rawat, Kinnari A. V.; Das, Sanjoy; Dvivedi, Sanjay; Rajan, Manu; Zaidi, Rihan (International Surgery Journal, 2018)
Background: Uttarakhand is a hilly state inhabited by various wild animals. Human encroachment into the forest areas has increased the encounters between humans and wild animals. Encounters have been on the rise and bear mauling seems to be one of the leading causes of wild animal attacks with grievous results. Methods: The study was conducted in the Department of Plastic and Reconstructive Surgery, Himalayan Institute of Medical Sciences (HIMS), Swami Ram Nagar, Dehradun, Uttarakhand, India from November 2016 to February 2017. After obtaining written informed consent from the patient a data pertaining to history of injury, time of hospital arrival, number of operative procedures, time of hospital stay, complications were recorded. Results: The injury timing of bear mauling was maximum during 12pm-8pm in 3 cases. Mean length of hospital stay was 19 days. Three cases (42.85%) of wound dehiscence were due to margin necrosis. Amongst the permanent damages suffered, were loss of vision in one eye in 1 case (14.28%), facial disfigurement in the form of contour deformities in 2 cases (28.57%), ectropion and facial nerve palsy in 1 case (14.28%) and parotid fistula in 1 case (14.28%). Conclusions: Encroachment and deforestation have led to an increase in injuries caused by the Himalayan black bears. Ominous effects seen in the changing climatic pattern largely due to global warming could be a possibility of causing altered living habitat for the bears in this Garhwal region getting more aggressive day by day.